Resistance analyses in HIV infected patients with a history of multiple antiretroviral treatment regimens. Issue 6 (1st December 2001) - Plettenberg, Andreas; Albrecht, Dirk; Lorenzen, Thore; Paech, Volker; Petersen, Heiko; Fenner, Thomas; Meyer, Thomas; Arndt, Rüdiger; Hertogs, Kurt; Pauwels, Rudi; Weitzel, Thomas; Stoehr, Albrecht
Abstract : Objective: To assess HIV-1 isolate based resistance profiles from extensively pretreated patients and effects of a resistance guided switch of antiretroviral therapy. Methods: In a prospective study phenotypic and genotypic resistance analyses were performed on HIV infected individuals with failure of the current therapy and history of at least three antiretroviral regimens. Antiretroviral therapy was changed according to the results. Viral load and CD4 lymphocyte counts were measured at baseline, after 10 (SD 2), and 24 (2) weeks. Results: All patients (n=52) failed their actual regimen. Currently versus ever previously taking the specific drug, resistance associated mutations and phenotypic resistance to AZT and 3TC were found in over 80% of individuals; resistance to DDI and D4T was detected in less than 10% of cases. A resistance guided switch of therapy was followed by a median decrease of viral load of 0.5 log10 units after 24 weeks. Individuals resistant to two or more drugs compared with patients with resistance to less than two drugs of ongoing treatment, were switched to a regimen containing DDI, D4T, and a PI or NNRTI. After 10 (SD 2) weeks viral load decrease was pronounced in patients with resistance to at least two drugs in the previous regimen. Conclusions: Among different RTI, the profile of clinically relevant resistance indicates pronounced differences when looking at separate drugs. Regarding virological response, in the context of available drugs, resistance tested with currently used methods is of limited value in extensively pretreated patients and seems to have its value primarily in first or second switch of therapy.